L’ile de Mozambique et l’influence de l’architecture européenne - Salema, Sofia (2015)
Portuguese settlement in Mozambique first took place in the early years of 16th century, after Vasco da Gama arrived to the Island of Mozambique in 1498. The Island was already inhabitated, and an important trading point of the oriental coast of Africa, cradlle of the rich Swahili Culture. Portuguese traders and arabian-swahili population struggled for years for the comercial domain of the island and the coast. In order to assure the domain of the Oriental Coast of Africa, the vice-King of India D. Francisco de Almeida is ordered to build the three fortresses of Sofala, Quiloa and Melinde. Thus protected, and also strengthned by its own complex defensive system, the island of Mozambique florishes; the small village grows and, in 1818, becomes a town and also the capital of Mozambique until 1898. As a town and capital by its own right, the island of Mozambique still remains, in present times, as a model of the intersection of several cultures, where the portuguese pattern prevails - in urban planning, in different architectonic models in religious, military and civil buildings, in decoration and building techniques - always with a strong influence of other cultures. The result is an eccletic architecture from 1500 to 19th century, showing undeniable european pattern, with the influence of swahili and indian models.